AUDIT MARKET CONCENTRATION ISSUES - Khachatryan, Gnel (Bulletin of Yerevan University G: Economics, 2019)
In this article, the world audit market concentration by the biggest audit network firms is investigated; as well as justification of applying auditors’ short-list for PIEs financial statements audits is analyzed. Professional research and analyses conclude that com-plying complex and continually developing requirements of the IFRSs and ISAs are out of capabilities of the auditors that are not members of the international big audit firm networks. This circumstance justifies the concentration of the audit market into the biggest global audit network firms. From the other side, applying auditors’ short-list could result in limiting the competitive market, as well as the society, could consider it as a nonjustified market limitation measure.